MAGICAL REALISM IN NEIL GAIMAN’S THE OCEAN AT THE END OF THE LANE NOVEL - Hasanah, Sa'adatil; Kuncara, Singgih Daru; Astuti, Anjar Dwi (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This research discusses magical realism in Neil Gaiman’s The Ocean at the End of the Lane. The purposes of this research are to find out the characteristics and literary techniques and to explain the role of magical realism that is portrayed in the novel. This research uses theories of characteristics of magical realism by Wendy B. Faris and literary techniques and role of magical realism by Anne C. Hegerfeldt. The method that is applied is descriptive qualitative and the approach is post-structuralism. The data are obtained from the dialogues and narrations that relate to the topics that are being analyzed. The result of the analysis shows that the five primary characteristics of magical realism are found in the novel like the irreducible elements of magic, unsettling doubts, phenomenal world, merging realms, and disruption of time/space/identity. It also shows that the five basic literary techniques of magical realism are represented within the novel such as the adaptation of other genres and modes, magical realist focalizer, paradigm of knowledge, strategies of destabilization, and techniques of literalization. The result also shows the role of magical realism that is portrayed through the influence of magical phenomena in the narrator/protagonist’s life.